Symptoms of Posttraumatic Stress Disorder are Associated with Exaggerated Neural Response to Surprising Errors. Issue 1 (6th October 2020) - Howlett, Jonathon R.; Bomyea, Jessica; Harlé, Katia M.; Simmons, Alan N.
Abstract: Posttraumatic stress disorder (PTSD) is characterized by exaggerated salience of previously innocuous cues and associated with hyperactivity of salience‐related brain regions. Recently, computational models have been deployed to operationalize salience more precisely regarding surprise‐driven learning, leading to findings that such learning is altered in anxiety‐related disorders. In the present study, a sample of 20 combat veterans completed a probabilistic learning task during fMRI scanning. We applied a computational model to generate a trial‐by‐trial surprise signal (i.e., unsigned prediction error or difference between the expected probability of an outcome and the actual observed outcome), which allowed us to examine the neural response to surprising events. We did not observe an association between PTSD symptoms and behavioral indices of learning in the task. Surprising errors were associated with increased activity in the left precuneus/inferior parietal lobule and right inferior parietal lobule, two parietal regions that are linked to salience processing. Additionally, PTSD symptom severity was positively associated with precuneus/inferior parietal lobule activation to surprising errors, r = .63, p = .004. Taken together, this pattern of results suggests that PTSD symptoms are specifically associated with an exaggerated response to surprising errors in salience‐related regions of the brain. This altered pattern of neural activity could represent a target for intervention to improve PTSD symptoms. 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯: JOTS‐19‐0329.R2_Howlett_cantonese Traditional Chinese 創傷後壓力症狀與對意外錯誤的誇張神經反應有關 摘要 : 創傷後壓力症(PTSD)的特徵是對先前無害線索的顯著性誇大, 並與顯著處理相關的大腦區域的過度活躍有關。最近, 計算模型被用來更精確地操作突發事件驅動的研究, 結果發現這種研究在焦慮相關的障礙中發生了改變。在本研究中, 20名退伍軍人在fMRI掃描期間完成了一項概率研究任務。我們應用一個計算模型來生成一個反覆試驗的意外信號(即無符號預測錯誤或結果的預期概率與實際觀察到的結果之間的差異), 這使我們能夠檢查對驚訝事件的神經反應。我們沒有觀察到創傷後壓力症狀和任務中研究的行為指數之間的聯繫。令人驚訝的錯誤與左側楔前/下頂葉和右側下頂葉的活動增加有關, 這兩個頂葉區域與顯著資訊處理有關。另外, 創傷後壓力症狀的嚴重程度與楔前/下頂葉對令人驚訝的錯誤的激活呈正相關, 為r =.63, p = .004。 綜上所述, 這種結果模式表明, 創傷後壓力症狀與大腦顯著處理相關區域對意外錯誤的誇張反應有關。這種神經活動的改變模式可能是干預改善創傷後壓力症狀的一個目標。 Simplified Chinese 创伤后压力症状与对意外错误的夸张神经反应有关 摘要 : 创伤后压力症(PTSD)的特征是对先前无害线索的显著性夸大, 并与显著处理相关的大脑区域的过度活跃有关。最近, 计算模型被用来更精确地操作突发事件驱动的研究, 结果发现这种研究在焦虑相关的障碍中发生了改变。在本研究中, 20名退伍军人在fMRI扫描期间完成了一项概率研究任务。我们应用一个计算模型来生成一个反复试验的意外信号(即无符号预测错误或结果的预期概率与实际观察到的结果之间的差异), 这使我们能够检查对惊讶事件的神经反应。我们没有观察到创伤后压力症状和任务中研究的行为指数之间的联系。令人惊讶的错误与左侧楔前/下顶叶和右侧下顶叶的活动增加有关, 这两个顶叶区域与显著信息处理有关。另外, 创伤后压力症状的严重程度与楔前/下顶叶对令人惊讶的错误的激活呈正相关, 为r =.63, p = .004。 综上所述, 这种结果模式表明, 创伤后压力症状与大脑显著处理相关区域对意外错误的夸张反应有关。这种神经活动的改变模式可能是干预改善创伤后压力症状的一个目标。